Gender differences in faculty rank among academic physicians: a systematic review and meta-analysis - Mohammed Al-Omran; Konrad Salata; Ben Li; Nancy N Baxter; Fahima Dossa; Teruko Kishibe; Elisa Greco; Jean Jacob-Brassard (BMJ Open, 2021)
Objective Many studies have analysed gender bias in academic medicine; however, no comprehensive synthesis of the literature has been performed. We conducted a pooled analysis of the difference in the proportion of men versus women with full professorship among academic physicians.Design Systematic review and meta-analysis.Data sources MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Education Resources Information Center and PsycINFO were searched from inception to 3 July 2020.Study selection All original studies reporting faculty rank stratified by gender worldwide were included.Data extraction and synthesis Study screening, data extraction and quality assessment were performed by two independent reviewers, with a third author resolving discrepancies. Meta-analysis was conducted using random-effects models.Results Our search yielded 5897 articles. 218 studies were included with 991 207 academic physician data points. Men were 2.77 times more likely to be full professors (182 271/643 790 men vs 30 349/251 501 women, OR 2.77, 95% CI 2.57 to 2.98). Although men practised for longer (median 18 vs 12 years, p<0.00002), the gender gap remained after pooling seven studies that adjusted for factors including time in practice, specialty, publications, h-index, additional PhD and institution (adjusted OR 1.83, 95% CI 1.04 to 3.20). Meta-regression by data collection year demonstrated improvement over time (p=0.0011); however, subgroup analysis showed that gender disparities remain significant in the 2010–2020 decade (OR 2.63, 95% CI 2.48 to 2.80). The gender gap was present across all specialties and both within and outside of North America. Men published more papers (mean difference 17.2, 95% CI 14.7 to 19.7), earned higher salaries (mean difference $33 256, 95% CI $25 969 to $40 542) and were more likely to be departmental chairs (OR 2.61, 95% CI 2.19 to 3.12).Conclusions Gender inequity in academic medicine exists across all specialties, geographical regions and multiple measures of success, including academic rank, publications, salary and leadership. Men are more likely than women to be full professors after controlling for experience, academic productivity and specialty. Although there has been some improvement over time, the gender disparity in faculty rank persists.PROSPERO registration number CRD42020197414.